2003
DOI: 10.1177/1541204002238365
|View full text |Cite
|
Sign up to set email alerts
|

The Recidivism of Violent Youths in Juvenile and Adult Court

Abstract: Contemporary research suggests that increased efforts to transfer juveniles to the adult criminal justice system may backfire because waived youths generally exhibit greater recidivism as compared to similar offenders retained in juvenile court. One concern with this research is the possibility of selection bias, meaning that the findings could be explained as merely a simple consequence of the highest risk youth being transferred. This study examined this issue for 494 violent youths from Pennsylvania, of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 32 publications
2
74
2
Order By: Relevance
“…Age was also another predictor for re-arrest. Contrary to previous studies (Myers, 2003; Trulson et al, 2005), our results indicate that older youth were more likely to be re-arrested than younger youth who are involved in the juvenile justice system. Older youth are more likely to have the opportunity to engage deviant behavior and delinquent acts than younger youth (Watson, 2007).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Age was also another predictor for re-arrest. Contrary to previous studies (Myers, 2003; Trulson et al, 2005), our results indicate that older youth were more likely to be re-arrested than younger youth who are involved in the juvenile justice system. Older youth are more likely to have the opportunity to engage deviant behavior and delinquent acts than younger youth (Watson, 2007).…”
Section: Discussioncontrasting
confidence: 99%
“…Minor et al's (1997) two-year follow-up study, which consisted of a group of 475 youth referred to a juvenile court for the first time, also found that younger juveniles were significantly more likely to be re-arrested than older youth. Myers (2003) examined the likelihood, seriousness, and timing of re-arrest for 494 violent youth offenders in Pennsylvania. Consistent with previous studies, Myers' (2003) findings also indicated that younger youth were more likely than older youth to be rearrested.…”
Section: Static Risk Factorsmentioning
confidence: 99%
“…They find higher recidivism rates among transferred youth (Myers 2003;Lanza-Kaduce et al 2005;Fagan, Kupchik, and Liberman 2007) and some evidence of treatment effect heterogeneity (Loughran et al 2010;Fagan, Kupchik, and Liberman 2007).…”
Section: Prior Literaturementioning
confidence: 99%
“…These findings raise important questions about the impact of incarceration on inmates' psychological correlates of (Ashkar & Kenny, 2008; Lambie & Randell, 2013; Lane et al, 2002;Myers, 2003). The traditional penitentiary treatment, together with the controls' harsh criminal features (e.g., longer sentence length), may be responsible for the observed deterioration in these subjects.…”
Section: **Insertmentioning
confidence: 94%
“…These findings raise important questions about the impact of incarceration on inmates' psychological correlates of antisocial behavior. The worrisome deterioration observed in controls over a one year period in variables such as anger, shame, and paranoia, raises the question of whether traditional prison practices work towards rehabilitation or may be bolstering psychological and emotional processes related to maladaptive behavior (Ashkar & Kenny, 2008;Lambie & Randell, 2013;Lane et al, 2002;Myers, 2003). The traditional penitentiary treatment, together with the controls' harsh criminal features (e.g., longer sentence length), may be responsible for the observed deterioration in these subjects.…”
Section: **Insertmentioning
confidence: 99%